Experience of military infectionists on working out and introduction of standards of diagnostics and treatment of infectious diseases - Yu. P. Finogeev; Yu. A. Vinakmen; V. F. Krumgolts; S. M. Zakharenko (Журнал инфектологии, 2014)
Any state not in a condition to allocate unlimited financial resources for medical maintenance of the population. In the conditions of restriction of financial possibilities, to enough stable and predicted number of the medical personnel, known equipment of medical institutions and population before the state there is the major problem of maintenance of rendering of optimum volume of diagnostic and medical services to the maximum number of citizens of the country. Search of the best balance between the advanced possibilities of medicine and really necessary level of rendering of medical services is actively conducted in our country during a placenta of decades. The certain contribution to working out of standards of diagnostics and treatment of infectious patients is brought by military infectionists